2019
DOI: 10.1021/acs.jpclett.9b01841
|View full text |Cite
|
Sign up to set email alerts
|

PbS Nanocrystals Made with Excess PbCl2 Have an Intrinsic Shell that Reduces Their Stokes Shift

Abstract: The use of excess PbCl2 in the synthesis of PbS nanocrystals has become a convenient route to produce narrow-line-width infrared emitters. However, these materials have found limited adoption in optoelectronic deviceseven compared to PbS nanocrystals prepared with lead oleate. Here, using both transmission electron microscopy and small-angle X-ray scattering, we show that excess PbCl2 results in larger-diameter PbS nanocrystals for the same excitonic features, which is consistent with the formation of an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…The surrounding PbI 2 matrix shell induces a tensile strain to expand the lattice constant, thereby shifting the Bragg peak to a smaller scattering angle. [ 38,43 ] In our case, the introduction of TBAI in the reaction can remove the excess PbI 2 in the QD film, which can release the tensile strain and shift the Bragg peak to a larger scattering angle, as seen in GIWAXS (Figure 2f). Consequently, GISAXS and GIWAXS results indicate that TBAI causes a better stacking behavior of the QDs in the final QD solid.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The surrounding PbI 2 matrix shell induces a tensile strain to expand the lattice constant, thereby shifting the Bragg peak to a smaller scattering angle. [ 38,43 ] In our case, the introduction of TBAI in the reaction can remove the excess PbI 2 in the QD film, which can release the tensile strain and shift the Bragg peak to a larger scattering angle, as seen in GIWAXS (Figure 2f). Consequently, GISAXS and GIWAXS results indicate that TBAI causes a better stacking behavior of the QDs in the final QD solid.…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, it is well established that the presence of PbX 2 shells on colloidal QD surface causes the lattice compression in the QDs, which could reflect the thickness and coverage of PbI 2 shells in our case. [38,39] We perform also grazing-incidence wide-angle X-ray scattering (GIWAXS) characterizations to monitor the strain in QD films (Figure 2d,e). For further analysis, azimuthal integrations are done as shown in Figure 2f.…”
mentioning
confidence: 99%
“…81,82 Furthermore, recent work has demonstrated that PbS NCs synthesized from PbCl2 have a PbCl2 rich surface, leading to improved photoluminescence quantum yield and chemical stability, which might be related to the passivation by a layer of the hereby reported Pb3S2Cl2 phase. [83][84][85] This hypothesis may stimulate further studies aiming at a more detailed characterization of those systems.…”
Section: Preliminary Investigation Of Iodide and Chloride-based Ncsmentioning
confidence: 91%
“…4a for comparison). 57,58 PbSe NPL samples were photoexcited at 700 nm (with an optical density of sample solutions of #0.1) and with comparable photoexcitation uence (30 mJ cm À2 ) to ensure a similar distribution of the number of photoexcited excitons in pristine and CdCl 2 treated PbSe NPL samples. 29 TA spectral line cuts at 10 ps aer photoexcitation shown in Fig.…”
Section: Papermentioning
confidence: 99%